Shivering in the Pleistocene. Human adaptations to cold exposure in Western Europe from MIS 14 to MIS 11. Issue 153 (April 2021) - Rodríguez, Jesús; Willmes, Christian; Mateos, Ana
Abstract: During the mid-Middle Pleistocene MIS 14 to MIS 11, humans spread through Western Europe from the Mediterranean peninsulas to the sub-Arctic region, and they did so not only during the warm periods but also during the glacial stages. In doing so, they were exposed to harsh environmental conditions, including low or extremely low temperatures. Here we review the distribution of archeological assemblages in Western Europe from MIS 14 to MIS 11 and obtain estimates of the climatic conditions at those localities. Estimates of the mean annual temperature, mean winter and summer temperatures, and the lowest temperature of the coldest month for each locality were obtained from the Oscillayers database. Our results show that hominins endured cold exposure not only during the glacial stages but also during the interglacials, with winter temperatures below 0 °C at many localities. The efficacy of the main physiological and behavioral adaptations that might have been used by the Middle Pleistocene hominins to cope with low temperatures is evaluated using a simple heat-loss model. Our results suggest that physiological and anatomical adaptations alone, such as increasing basal metabolic rate and subcutaneous adipose tissue, were not enough to tolerate the low winter temperatures of Western Europe, even during the MIS 13 and MIS 11 interglacials. In contrast, the use of a simple fur bed cover appears to have been an extremely effective response to low temperatures. We suggest that advanced fire production and control technology were not necessary for the colonization of northern Europe during MIS 14 and MIS 12. We propose that Middle Pleistocene European populations were able to endure the low temperatures of those glacial stages combining anatomical and physiological adaptations with behavioral responses, such as the use of shelter and simple fur clothes. Highlights: European hominins lived under very cold conditions during MIS 14 and MIS12. Hominins endured cold combining physiological, anatomical, and behavioral responses. Sleeping under fur bed covers was likely a key adaptation in cold climates. Fire control was not an essential requirement to colonize northern Europe.